Multi-omics insights into biomarkers of breast cancer associated diabetes: a computational approach - Loganathan, Tamizhini; Doss, C. George Priya (Frontiers in Medicine, 2025)
IntroductionBreast cancer (BC) and diabetes are multifaceted diseases with interconnected molecular mechanisms that are not yet fully elucidated. These diseases share common risk factors, biological pathways, and treatment outcomes.MethodsThis study utilizes an integrative computational approach to investigate the interplay between BC and diabetes in African American (AA) and European American (EA) cohorts. It employs transcriptomic and exomic analyses to identify shared pathways and potential therapeutic targets.ResultsThe pooled cohort of differential expression analysis identified 2,815 genes differentially expressed in BC patients with diabetes compared to those without diabetes, including 1824 upregulated and 990 downregulated genes. We reanalyzed transcriptomic data by stratifying BC patients with and without diabetes into two cohorts, identifying 3,245 DEGs in AA and 3,208 DEGs in EA, with 786 genes commonly altered between both groups. Whole-exome sequencing (WES) of 23 BC patients with diabetes revealed 899 variants across 208 unique genes, predominantly missense mutations. Among these, nine key genes were prioritized, with TNFRSF1B (L264P) and PDPN (A105G) identified as the most deleterious variants. Functional enrichment analyses highlighted the significant involvement of pathways related to extracellular matrix organization, angiogenesis, immune regulation, and signaling processes critical to cancer progression and metabolic dysfunction. The TNF pathway emerged as a central link connecting chronic inflammation, insulin resistance, and tumor growth. TNF-mediated mechanisms, including NF-κB activation, oxidative stress, and epithelial-to-mesenchymal transition (EMT), were found to drive both diseases, promoting tumorigenesis, immune evasion, and metabolic dysregulation.ConclusionThis study provides critical molecular insights into the shared mechanisms of BC and diabetes, identifying the TNF pathway as a key therapeutic target to improve outcomes for patients with these interconnected conditions.